Arquétipos e autenticidade: malefícios do uso superficial pelas marcas - SANTOS, Agatha Maria da Silva (157, 2025)
Há um crescente interesse por estratégias de branding para utilizar os arquétipos de marca, mas podemos observar que há o uso crescente desses elementos de forma superficial,o que gera um impacto simbólico nessas narrativas. O respectivo artigo busca evidenciar como os arquétipos são utilizados na construção de uma marca, utilizando fundamentação teórica de autores chaves como Carl Jung (1969), Gilmore e Pine (2007), entre outros. A metodologia usada foi a revisão sistemática, que utilizou ferramentas como o Google Acadêmico como base para identificar obras com relevância para a pesquisa. Há um estudo de caso comparativo entre duas grandes marcas que possuem abordagens convergentes ao utilizar os arquétipos. Com a contribuição do respectivo artigo ficou evidente a necessidade de se utilizar essas simbologias de maneira estratégica, enraizada na cultura e valores da marca.

There is a growing interest in branding strategies that use brand archetypes, especially due to consumers' recurrent search for connections with real and authentic brands. However, we can observe that these elements are increasingly being used superficially, aesthetically and without real values, which generates a symbolic impact on these narratives. Often, when used incorrectly, reduced to commercial labels, they bring several risks to the brand, including a lack of commitment and disconnection with the consumer. The objective of this work is to analyze in a detailed and critical way how archetypes are used in the construction of a brand, using theoretical foundations from key authors such as Carl Jung (1969), Gilmore and Pine (2007), among others. The methodology used was a systematic review of the literature, which used tools such as Google Scholar as a basis to identify works with excellent theoretical foundations and relevance to the research. There is a comparative case study between a Pepsi advertising campaign and the market positioning of Harley-Davidson, two major brands that have convergent approaches when using archetypes in different ways. With the contribution of the respective article, the need to use these symbols in a strategic way, rooted in the brand's culture and values, became evident.
Archetypes and authenticity: harmful use of surfaces by brands
Keywords: Marcas; Marketing; Gestão e Negócios